2022
DOI: 10.1111/nan.12799
|View full text |Cite
|
Sign up to set email alerts
|

The S1PR2‐CCL2‐BDNF‐TrkB pathway mediates neuroinflammation and motor incoordination in hyperammonaemia

Abstract: Aims: Chronic hyperammonaemia and inflammation synergistically induce neurological impairment, including motor incoordination, in hepatic encephalopathy. Hyperammonaemic rats show neuroinflammation in the cerebellum which enhances GABAergic neurotransmission leading to motor incoordination. We aimed to identify underlying mechanisms. The aims were (1) to assess if S1PR2 is involved in microglial and astrocytic activation in the cerebellum of hyperammonaemic rats; (2) to identify pathways by which enhanced S1PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 112 publications
3
44
0
Order By: Relevance
“…The increased content of CCL2 induced by HA-EVs in cerebellar slices from control rats is associated with increased membrane expression and activation of its receptor CCR2 which increases BDNF in activated microglia ( Figure 7 ), in agreement with the effects reported in cerebellum of hyperammonemic rats by Arenas et al ( 22 ). The increased levels of BDNF result in increased content, membrane expression and activation of its receptor TrkB ( Figure 7 ).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The increased content of CCL2 induced by HA-EVs in cerebellar slices from control rats is associated with increased membrane expression and activation of its receptor CCR2 which increases BDNF in activated microglia ( Figure 7 ), in agreement with the effects reported in cerebellum of hyperammonemic rats by Arenas et al ( 22 ). The increased levels of BDNF result in increased content, membrane expression and activation of its receptor TrkB ( Figure 7 ).…”
Section: Discussionsupporting
confidence: 91%
“…We have recently shown that microglia activation in cerebellum of hyperammonemic rats is mediated by enhanced membrane expression and activation of TNFR1, which increases CCL2 production in Purkinje neurons which in turn increases activation and CCR2 membrane expression, leading to increased BDNF in microglia. BDNF released from activated microglia increases activation and membrane expression of TrkB which, in turn, enhances membrane expression of the chloride co-transporter KCC2, increasing the chloride gradient and GABAergic neurotransmission ( 22 , see Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations